Contemporary Value Systems in China - Han, Zhen (China Insights,, 2018)
This work illustrates China's values and how they are practiced. After introducing readers to the theories, systematical structure, historical status, and influence of traditional Chinese values, it points out major developmental trends in connection with modernization. Further, it explores the significance of the contemporary reconstruction of Chinese values and argues that these values can be divided into three layers: values-based goals of national development, Chinese values concepts, and norms of values in a civil society. On this basis, it subsequently interprets the core socialist values "Prosperity, Democracy, Civility and Harmony," the value concepts "Freedom, Equality, Justice and Rule of Law" and values-based norms "Patriotism, Dedication, Integrity and Friendship.".